THE RELATIONSHIP BETWEEN MACRONUTRIENT AND MICRONUTRIENT INTAKE ON CED IN ADOLESCENT GIRLS IN MAN 1 ACEH BARAT - Putri Rahma Aulia; Enda silvia Putri; Itza Mulyani; Hanif Muchdatul Ayunda (PT. Radja Intercontinental Publishing, 2024)
Chronic Energy Deficiency (CED) is a condition when a person experiences chronic malnutrition that causes health problems in adolescent girls, with an Upper Arm Circumference (LILA) size of less than 23.5 cm. Based on the results of initial observations made by researchers by observing several high schools, after researchers observed that in MAN 1 West Aceh there were several young women with CED justification. This study aims to determine the relationship between macronutrient and micronutrient intake on the incidence of Chronic Energy Deficiency (CED) in adolescent girls in MAN 1 West Aceh. The research method uses a cross-sectional approach carried out in MAN 1 West Aceh. Proportionnate Stratified Random Sampling sampling technique with a total of 261 people in MAN 1 West Aceh. The instrument used is the Semi Quantitative Food Frequency Questionnaire. Data analysis using Chi Square Test and Logistic Regression. The results showed that there was a significant relationship between carbohydrate, protein, fat intake and CED in adolescent girls with a p-value of 0.000 (p<0.05), there was no significant relationship between iron and CED in adolescent girls with a p-value of 0.083 (p>0.05), there was no significant relationship between calcium and CED in adolescent girls with a p-value of 0.735 (p>0.05), There was no significant association between zinc and CED in adolescent girls with a p-value of 0.374 (p>0.05). Based on the results of research and discussion, it can be concluded that there is a relationship between macronutrient intake of CEDs in adolescent girls with p-value (<0.05), while micronutrient intake has no significant relationship with CED in adolescent girls with p-value (>0.05). Itis hoped that the school can carry out nutritional status assessment activities for students so that information and education can be provided related to the importance of paying attention to the nutritional status of female students who fall into the category of women of childbearing age (WUS) for health preparation and nutritional status in adulthood. It is better for teenagers to pay attention to a good diet according to their needs.